#### Answer

$\cos ^{2}\theta \sin ^{2}\theta $

#### Work Step by Step

$\dfrac {1-\sin ^{2}\left( -\theta \right) }{1+\cot ^{2}\left( -\theta \right) }=\dfrac {1-\left( \sin \left( -\theta \right) \right) ^{2}}{1+\dfrac {\cos ^{2}\left( -\theta \right) }{\sin ^{2}\left( -\theta \right) }}=\dfrac {1-\left( -\sin \theta \right) ^{2}}{1+\dfrac {\cos ^{2}\theta }{\left( -\sin \theta \right) ^{2}}}=\dfrac {\cos ^{2}\theta }{1+\dfrac {\cos ^{2}\theta }{\sin ^{2}\theta }}=\dfrac {\cos ^{2}\theta \sin ^{2}\theta }{\cos ^{2}\theta +\sin ^{2}\theta }=\cos ^{2}\theta \sin ^{2}\theta $